TIPE PEMISAHAN DAN PENGARUHNYA TERHADAP NILAI ASET BANK UMUM SYARIAH HASIL PEMISAHAN - Al Arif, M. Nur Rianto (KINERJA, 2014)
The objective of this research is to analyze the impact of spinoff type to total asset in spinoffs banks.The analysis technique used in this paper is panel regression with fixed effect model. The result shows that thespinoff type didn’t have an influence to total asset in spinoffs banks. This research also shows that the spinoffpolicy is to be evaluated because the economy of scale from the existing Islamic business units is still small. Thespinoff policy is one of the business strategies that can be done to develop the Islamic banking industry, but thispolicy is not the final goal of Islamic banking industry. The most important thing today is to create a healthy andcompetitive Islamic banking industry.Keywords: spinoff type; panel regression; islamic banks, bank asset